2002
DOI: 10.1161/hy0302.105681
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Modulation of Neurally Induced Proximal Tubular Fluid Reabsorption in the Rat

Abstract: Abstract-This study investigated the role of NO in mediating the renal sympathetic nerve-mediated increases in proximal tubular fluid reabsorption (Jva). In inactin-anesthetized Wistar rats, renal sympathetic nerve stimulation (15 V, 2 ms) at 0.75 and 1.0 Hz did not change blood pressure or glomerular filtration rate but did decrease urine flow and sodium excretion in a frequency-related fashion by 40% to 50% at 1.0 Hz (both, PϽ0.01). Renal nerve stimulation in control animals increased Jva by 11% at 0.75 Hz (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…Thus ANG II stimulates neuronal NOS and renal interstitial cGMP production, probably via the AT 2 receptor (52), and recent work by Zhang and Mayeux (65) shows that neuronal NOS-derived NO is triggered beyond a certain ANG II threshold concentration, thereby counteracting the stimulatory effect on the Na-K-ATPase. Similarly, studies have shown that NO exerts a tonic inhibitory action on nervemediated proximal tubular reabsorption, and at the same time NO exerts a facilitatory role in norepinephrine release (55,61,62). Altogether these experiments show that NO is an integrated modulating agent in renal proximal tubular function, further studies on the interaction between the NO system and other modulators of proximal tubular sodium handling in cirrhosis are warranted.…”
Section: Discussionmentioning
confidence: 76%
“…Thus ANG II stimulates neuronal NOS and renal interstitial cGMP production, probably via the AT 2 receptor (52), and recent work by Zhang and Mayeux (65) shows that neuronal NOS-derived NO is triggered beyond a certain ANG II threshold concentration, thereby counteracting the stimulatory effect on the Na-K-ATPase. Similarly, studies have shown that NO exerts a tonic inhibitory action on nervemediated proximal tubular reabsorption, and at the same time NO exerts a facilitatory role in norepinephrine release (55,61,62). Altogether these experiments show that NO is an integrated modulating agent in renal proximal tubular function, further studies on the interaction between the NO system and other modulators of proximal tubular sodium handling in cirrhosis are warranted.…”
Section: Discussionmentioning
confidence: 76%
“…Several reports implicate a role for nNOS to attenuate tubuloglomeruler feedback (TGF) (36,43); however, one would expect an increase in blood pressure due to an enhanced TGF response following nNOS inhibition. Johns and colleagues (4,44) found that nNOS inhibition attenuated the response of renal nerve stimulation on sodium excretion, suggesting a facilitory role for NO on adrenergic release. In this regard, Cervenka et al (8) demonstrated increased sodium excretion following acute nNOS inhibition in intact but not denervated male mRen(2)27 rats, the founder strain to the current congenic strain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NO has bidirectional roles in mediating or modulating renal sympathetic nerve action. In the proximal tubules, it may mediate the sodium-retaining effects of sympathetic nerves (370), whereas it may blunt the neural effects in isolated perfused rat kidney and in the renal medulla (62,266).…”
Section: Role Of Renal Oxidative Stress In Hypertension 2069mentioning
confidence: 99%